2015
DOI: 10.1016/j.inoche.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening gold–gold bonds by complexing gold clusters with noble gases

Abstract: We report an unexpectedly strong and complex chemical bonding of rare-gas atoms to neutral gold clusters. The bonding features are consistently reproduced at different levels of approximation within density-functional theory and beyond: from GGA, through hybrid and double-hybrid functionals, up to renormalized secondorder perturbation theory. The main finding is that the adsorption of Ar, Kr, and Xe reduces electron-electron repulsion within gold dimer, causing strengthening of the Au\Au bond. Differently from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
0
14
0
4
Order By: Relevance
“…At the CCSD(T)/aug‐cc‐pVQZ level, the Ne−Au bond strength was recorded as 2.1 kcal/mol. In a relevant work on Ng interaction with neutral cluster, Ghiringhelli and Levchenko observed an interesting phenomenon. Through their experimental and theoretical studies, they found that the absorption of Ng (Ar−Xe) reduces the electron‐electron repulsion in Au 2 and, hence, it strengthens this bond.…”
Section: Aftermath Of the Achievements In 2000mentioning
confidence: 93%
“…At the CCSD(T)/aug‐cc‐pVQZ level, the Ne−Au bond strength was recorded as 2.1 kcal/mol. In a relevant work on Ng interaction with neutral cluster, Ghiringhelli and Levchenko observed an interesting phenomenon. Through their experimental and theoretical studies, they found that the absorption of Ng (Ar−Xe) reduces the electron‐electron repulsion in Au 2 and, hence, it strengthens this bond.…”
Section: Aftermath Of the Achievements In 2000mentioning
confidence: 93%
“…[29] But for the closed-shell gold dimer Au 2 ,as trengthening of the AuÀAu bond is observed upon absorbing Kr, resulting in significantly influenced IR spectra, pointing to an increased covalent character. [30] On this basis,the goal of this study is to shed light on the Au + À Ng closed-shell interaction with the help of Ar complexes of mixed AuÀAg trimer cations by means of experimental IR spectra and DFT calculations.…”
mentioning
confidence: 99%
“…In diesen linearen Molekülen ( C ∞v , D ∞h Symmetrie) wurde eine geringfügige Verkürzung der Au‐Au‐Abstände von 2.429 (für Au 2 ) auf 2.421 und 2.40 Å (für Au 2 ⋅Kr bzw. Au 2 ⋅Kr 2 ) berechnet (MP2‐Rechnungen) …”
Section: Eckdaten Für Gold‐gold‐bindungen In Zweikernigen Au0‐ Und Auunclassified
“…Für Au 2 gibt es offensichtlich einen deutlichen Unterschied zwischen diesen berechneten und dem experimentellen Wert von 2.4715 Å (siehe oben). In älteren und jüngeren theoretischen Untersuchungen von Au 2 werden Daten um die 2.50 Å (MP2) und wieder solche am kürzeren Ende (MP2: 2.429 Å) erhalten . Diese Diskrepanz ist momentan noch unerklärt.…”
Section: Eckdaten Für Gold‐gold‐bindungen In Zweikernigen Au0‐ Und Auunclassified